The Historic Advisory Opinion on Palestine: An Overview of Indonesia's Submissions and the Way Forward - Rosandry, Indra; Taborat, Aloysius Selwas; Adiputra, Kadek Denny Baskara (UI Scholars Hub, 2025)
On 19 July 2024, the International Court of Justice (ICJ) rendered a historic ruling which declared that Israel’s presence in the Occupied Palestinian Territory (OPT) is unlawful. While this historic Advisory Opinion on the Legal Consequences Arising from Israel’s Policies and Practices in the OPT, including East Jerusalem (Advisory Opinion) should be celebrated, much more needs to be done in order to fully realize the decisions contained therein. This article presents an overview of the Republic of Indonesia’s legal arguments submitted to the ICJ concerning the request for an Advisory Opinion. Indonesia, a staunch supporter of the Palestinian cause, contends that Israel’s policies and practices constitute violations of international law, particularly due to its prolonged and illegal occupation over the OPT. This article seeks to analyze Indonesia’s submissions to the ICJ in light of the Advisory Opinion rendered, and looks at previous practices of the ICJ regarding advisory opinions to shed light on the way forward.